ANALYSIS OF TECHNO-ECONOMIC PLANNING OF ON-GRID ROOFTOP PV SYSTEM AT THE GOVERNMENT HOUSE OF PACITAN REGENCY - Ansori, Tirangga; Setiawan, Ahamd Agus; Wilopo, Wahyu (ASEAN Journal of Systems Engineering, 2022)
The geographical condition, which is relatively difficult to reach, electricity and infrastructure has not been maximized, making the electrification ratio in Pacitan Regency one of the lowest on the island of Java at 65%. Pacitan Regency has a promising renewable energy potential, but it has not been maximized for the benefit of the residents. One of them is a solar power plant. If used properly, this alternative energy source can be a solution to meet energy needs in remote areas. As part of the Government's efforts to achieve the new and renewable energy (RE) target of 23% by 2025, the Ministry of Energy and Mineral Resources has issued Minister of Energy and Mineral Resources Regulation Number 26 of 2021 concerning Connected Rooftop Solar Power Plants. On the Electric Power Network, the Holder of a Business License for the Provision of Electric Power for Public Interest (IUPTLU). This Ministerial Regulation is a refinement of the previous regulation to improve the governance and economics of PV, especially PV Rooftop. This regulation is also a step to respond to the existing dynamics and facilitate the public's desire to obtain electricity from renewable energy sources, as well as the desire to contribute to reducing greenhouse gas emissions. This study was conducted to calculate the optimum potential of rooftop photovoltaic power plants in the official residence of the Pacitan Regency Government as an alternative energy source to supply the electricity system from the official residence. This simulation was carried out using the System Advisor Model (SAM) software, considering the technical and economic aspects. Where the economic calculation has two scenarios, namely the profit value based on the Minister of Energy and Mineral Resources Regulation No. 26 of 2021 and the Minister of Energy and Mineral Resources No. 49 of 2018 with total energy produced of 13012 kWh / year with a total of 20 modules installed with a slope of 20o facing north and 1 Inverter and an LCOE value of Rp. 1231.31/kWh, and an NPV of Rp. 117,579,325.50.